PERAN PENDIDIKAN REALISME DALAM MEMBANGUN KEMAMPUAN BERPIKIR OBJEKTIF PESERTA DIDIK DI ERA DIGITAL - Shobihah, Anisah; Rizqi Prasetyo , Muhammad; Fuad Zaka, Muhammad; Muhlisin, Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has resulted in changes in various areas of life, including the educational process and the way students access information. The ease of obtaining information through various digital platforms requires students to have the ability to think objectively in order to be able to assess the truth of information rationally and remain firm despite various opinions and misleading data. This study aims to examine the contribution of realism education in developing students' objective thinking skills in the digital era. The research approach is qualitative with a focus on literature studies. Literature reviews are conducted from various academic sources, including scientific journals, scientific articles, and literature that refer to the theme of the study. Data analysis was carried out descriptively through the process of study, grouping, and synthesizing various studies on realism education and improving objective thinking skills. The findings of the study show that realism education has an important factor in building a way of thinking based on reality, empirical evidence, and logical reasoning. This approach encourages students to understand a phenomenon based on observation, direct experience, and scientifically accountable evidence. In addition, realism values also support the improvement of digital literacy through the ability to check the validity of information, recognize biases, and evaluate various sources of information available in the digital space. The application of realism education through project-based learning activities, investigations, real problem solving, and case studies provides opportunities for students to hone analytical, responsive, and decision-making skills objectively. In the midst of the rampant spread of hoaxes, disinformation, and various forms of information manipulation, realism education can be an effective foundation in helping students understand reality more accurately. Therefore, realism education is considered relevant to be applied in learning to form a generation that is able to think critically, objectively, and responsibly in responding to information technology developments.